Bibliometric Analysis of Electronic Student Worksheets Research Trends in Physics Learning in Indonesia - Mutiara Kharisma Riadhi; Hidayati Hidayati; Fatni Mufit; Selma Riyasni (Jurnal Penelitian Pembelajaran Fisika, 2025)
The rapid development of technology in education encourages the use of digital learning materials such as the Electronic Student Worksheets to improve the effectiveness of physics learning. However, comprehensive mapping of Electronic Student Worksheets research trends in Indonesia remains limited. This study aims to analyze publication trends, research characteristics, topic relationships, and identify research gaps related to Electronic Student Worksheets in physics learning in Indonesia. This research employs a bibliometric analysis approach by integrating the PRISMA method as a guideline for the identification, screening, and eligibility assessment of articles. Data were collected from Google Scholar and Scopus databases using the keyword. “Electronic Student Worksheets” and “Physics Learning,” covering the period 2020–202. Through the PRISMA flow, 506 eligible articles were obtained after screening and removing duplicates. Data analysis was conducted using Publish or Perish (PoP) and VOSviewer software through three visualization types: network visualization, overlay visualization, and density visualization to explore keyword relationships, topic trends, and research density. The results show that Electronic Student Worksheets publications have increased significantly since 2022, dominated by studies at the senior high school level and using applications such as Augmented Reality, Flip PDF, Wizer, Phet, and Liveworksheet, meanwhile the learning models that are often integrated are Problem Based Learning and Project Based Learning. Seventeen topic clusters and seventy-nine keywords were identified, with emerging themes including differentiated learning, socio scientific issues, and renewable energy material. The study concludes that Electronic Student Worksheets research trends are growing rapidly but remain limited to specific education levels and general topics. Future researchers are advised to expand the scope to vocational and higher education levels and explore teacher involvement in the development and implementation of Electronic Student Worksheets in Indonesia.